Magnetic field penetration in MgB2 single crystals: pinning and Meissner holes - Chabanenko, V.; Katrych, S.; Zhigadlo, N.D.; Karpinski, J.; Pérez-Rodríguez, F.; Cortés-Maldonado, R.; Abal’osheva, I.; Mikheenko, P.; Yurchenko, V.V.; Kuchuk, E.; Puźniak, R. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
The evolution of flux distribution in MgB2 single crystals during their remagnetization was imaged with magneto-optical technique. Meissner holes, formed as the areas where the annihilation of vortices and antivortices takes place, were found at the boundary between oppositely magnetized parts of the crystal. Gradient of magnetic induction in the vicinity of Meissner holes was found to be enhanced. Finger-like structures of convex shape, formed during the penetration of magnetic flux inside the crystal, were observed and explained as an effect of inhomogeneous pinning and demagnetizing field redistribution in the sample.